2021
DOI: 10.1108/intr-10-2019-0412
|View full text |Cite
|
Sign up to set email alerts
|

Others' fortune in online vs offline settings: how envy affects people's intention to share information

Abstract: PurposeThis paper aims to fill a gap in the existing literature by answering the following question: is the effect of envy on people's intention to share information the same in offline settings and on online social networks?Design/methodology/approachTwo studies demonstrate (1) how envy that results from upward social comparisons affects people's intention to share information and (2) the difference between online and offline settings.FindingsThe likelihood of sharing information susceptible of triggering env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…For RQ4, considering offline-to-online in an omni-channel, Suárez Vázquez and Chica Serrano (2021) found that, regardless of channel structure, showrooms can generate benefits for manufacturers, retailers and the overall omni-channel supply chain. Swoboda and Winters (2020) analyzed the reciprocal effect between channel images of major purchasing channels and how they affect consumer loyalty.…”
Section: Discussionmentioning
confidence: 99%
“…For RQ4, considering offline-to-online in an omni-channel, Suárez Vázquez and Chica Serrano (2021) found that, regardless of channel structure, showrooms can generate benefits for manufacturers, retailers and the overall omni-channel supply chain. Swoboda and Winters (2020) analyzed the reciprocal effect between channel images of major purchasing channels and how they affect consumer loyalty.…”
Section: Discussionmentioning
confidence: 99%